A Critique of the Philosophy of Social Sciences: Towards Pragmatism - Mahdi Hoseinzade Yazdi; Mohsen Mollabashi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Patrick Baert believes that although there are many capabilities in the field of philosophy of social sciences, pragmatism has not come to its proper place yet due to lack of enough attention on behalf of philosophers. He believes that pragmatism can be used properly in this field, and new prospects in social sciences may be discovered by its assistance. In his Philosophy of the Social Sciences: Towards Pragmatism and due to his criticisms on social sciences and philosophy of social sciences, Baert claims that one of his purposes in the book is to develop a new approach in philosophy of social sciences employing pragmatism. This article is going to explore his claim; before discussing the content, it has scanned all the chapters and analyzed Persian structure and translation of the book. At last and through content review and scrutiny of author’s claim it is concluded the book achievement is far from author’s assertion and his suggestions have no meaningful difference with expressions of hermeneutics, interpreters, instrumentalists, and followers of critical school and Baert have innovated nothing new and commenced no novel path for social sciences.